Hydrodynamic and hydro acoustic analysis of marine propeller in off design flow conditions - Ammar Nazeer; Niaz Bahadur Khan; Emad Uddin; Mohammed Jameel; Omar Al-Abbasi; Qian Wu; Adnan Munir; Hanzla Shahid (PLoS ONE, 2025)
This study provides a comprehensive analysis of the INSEAN E-779A four-bladed marine propeller, addressing both hydrodynamic and hydroacoustic aspects. Employing unsteady Reynolds-Averaged Navier-Stokes (RANS) simulations with the k-ω SST turbulence model for hydrodynamics and the Ffowcs Williams-Hawking acoustic analogy for acoustics. A wide range of operational conditions are examined by varying the advance ratio from 0.6 to 0.9 and flow incidence angle from 0 to 40 degrees. Computation of hydrodynamic coefficients across spatial directions provides insight into loading impacts on performance. Significant efficiency reductions are observed, such as a decrease from 64% to 28% at 40 degrees for an advance ratio of 0.88. Directional acoustic pressure distributions reveal notable variance, including a 19–31% change when reducing the advance ratio to 0.6 at 40 degrees incidence. Fast Fourier Transform (FFT) analysis of acoustic signals highlights dominant frequencies and acoustic signature changes downstream of the propeller. Notably, peak Sound Pressure Level (SPL) values at specific locations in the propeller’s wake demonstrating sensitivity to flow conditions. The investigation extends to near-field and far-field acoustic signatures, contributing to a comprehensive understanding of how acoustic behavior evolves with distance.